Biochar-Modified BiOBr Photocatalyst for Enhanced Visible-Light-Driven Degradation of Antibiotics - Yue Zhang; Yanlin Wu; Defa Hou; Xijuan Chai (International Journal of Environmental Research, 2026)

Spiral wrapped in-situ optic fiber tract - Hai Fu; Huifeng Yang; Xin Qiu; Zhi Chen; Yao Zhu; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2026)

Corrigendum to “Analysis and optimization of opening characteristics of deep-sea water hydraulic safety valve” [Ocean Eng. 344, 15 (January 2026), 123682] - Jize Jiang; Jiefu Liu; Jiangxiong Li; Boyang Zhang; Xiguang Hu; Yinshui Liu; Defa Wu (Ocean Engineering, 2026)

Analysis and optimization of opening characteristics of deep-sea water hydraulic safety valve - Jize Jiang; Jiefu Liu; Jiangxiong Li; Boyang Zhang; Xiguang Hu; Yinshui Liu; Defa Wu (Ocean Engineering, 2026)

Single-electrode multiplex sensing via metal ion displacement method - Yiming Zhang; Zhi Chen; Songrui Wei; Huiling Lin; Yujun Zhang; Yingxia Liu; Jing Wang; Qi Gao; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

Comparison of the Variability of Small Extracellular Vesicles Derived from Human Liver Cancer Tissues and Cultured from the Tissue Explants Based on a Simple Enrichment Method - Jie Chen; Zhigang Jiao; Jianwen Mo; Defa Huang; Zhengzhe Li; Wenjuan Zhang; Tong Yang; Minghong Zhao; Fangfang Xie; Die Hu; Xiaoxing Wang; Xiaomei Yi; et al. (Stem Cell Reviews and Reports, 2022)
A potential use of small extracellular vesicles (sEVs) for diagnostic and therapeutic purposes has recently generated a great interest. sEVs, when purified directly from various tissues with proper procedures, can reflect the physiological and pathological state of the organism. However, the quality of sEV is affected by many factors during isolation, including separation of sEV from cell and tissues debris, the use of enzymes for tissue digestion, and the storage state of tissues. In the present study, we established an assay for the isolation and purification of liver cancer tissues-derived sEVs (tdsEVs) and cultured explants-derived sEVs (cedsEVs) by comparing the quality of sEVs derived from different concentration of digestion enzyme and incubation time. The nano-flow cytometry (NanoFCM) showed that the isolated tdsEVs by our method are purer than those obtained from differential ultracentrifugation. Our study thus establishes a simple and effective approach for isolation of high-quality sEVs that can be used for analysis of their constituents. Graphical abstract

Metabolic characteristics and nutrient utilization in high-feed-efficiency pigs selected using different feed conversion ratio models - Beibei He; Tiantian Li; Wei Wang; Hang Gao; Yu Bai; Shuai Zhang; Jianjun Zang; Defa Li; Junjun Wang (Science China Life Sciences, 2019)

Effects of CTR4 deletion on virulence and stress response in Cryptococcus neoformans - Ping Zhang; Defa Zhang; Xueru Zhao; Dongsheng Wei; Yu Wang; Xudong Zhu (Antonie van Leeuwenhoek, 2016)